Rapid on-site evaluation of touch imprints of medical thoracoscopy biopsy tissue for the management of pleural disease - Wang, Hansheng; Liu, Yan; Wang, Jiankun; Ren, Tao; Luo, Guoshi; You, Hui; Wang, Xiao; Li, Dan; Wang, Lei; Wang, Meifang (Frontiers in Medicine, 2023)
Background and Objective: Medical thoracoscopy (MT) plays an important role in the diagnosis and treatment of pleural diseases, and rapid on-site evaluation (ROSE) has long been used for transbronchial needle aspiration or fine-needle aspiration to evaluate the adequacy of biopsy materials for the diagnosis of peripheral lung lesions. However, research on ROSE combined with medical thoracoscopy for the management of pleural disease has been rarely reported. We aimed to evaluate the diagnostic performance of ROSE for pleura biopsies and visual diagnosis by thoracoscopists for gross thoracoscopic appearance. The secondary objective was to assess the intermodality agreement between ROSE and final histopathologic diagnosis. Methods: A total of 579 patients with exudative pleural effusion (EPE) who underwent medical thoracoscopy combined with ROSE from February 2017 to December 2020 at Taihe Hospital were included in the study. Thoracoscopists’ visual diagnosis of gross thoracoscopic appearance, ROSE results, histopathologic findings and final diagnosis were recorded. Results: Thoracoscopic pleural biopsies were performed in 565 patients (97.6%); 183 patients were confirmed to have malignant pleural effusion (MPE), and 382 patients were confirmed to have benign pleural effusion (BPE). The area under the curve of ROSE for the diagnosis of MPE was 0.96 (95% CI: 0.94–0.98, p < 0.001), with a sensitivity of 98.7%, specificity of 97.2%, diagnostic accuracy of 97.1%, positive predictive value of 97.2% and negative predictive value of 97.2%. Diagnostic consistency between ROSE and histopathology was good (κ ± SE = 0.93 ± 0.02, p < 0.001). The area under the curve of the thoracoscopists’ visual diagnosis of gross thoracoscopic appearance was 0.79 (95% CI: 0.75–0.83, p < 0.01), with a sensitivity of 76.7%, specificity of 80.9%, positive predictive value of 62.4% and negative predictive value of 89.3%. Conclusion: ROSE of touch imprints of medical thoracoscopy biopsy tissue during MT showed high accuracy for distinguishing between benign and malignant lesions. In addition, ROSE was in good agreement with the histopathological diagnosis, which may help thoracoscopists perform pleurodesis (talc poudrage) directly during the procedure, especially in patients with malignant results.